The lying life of adults [large type] - Ferrante, Elena (Thorndike Press large print core, 2020)
"Giovanna's pretty face is changing, turning ugly, at least so her father thinks. Giovanna, he says, looks more like her Aunt Vittoria every day. But can it be true? Is she really changing? Is she turning into her Aunt Vittoria, a woman she hardly knows but whom her mother and father clearly despise? Surely there is a mirror somewhere in which she can see herself as she truly is. Giovanna is searching for her reflection in two kindred cities that fear and detest one another: Naples of the heights, which assumes a mask of refinement, and Naples of the depths, a place of excess and vulgarity. She moves from one to the other in search of the truth, but neither city seems to offer answers or escape"--